Comparison between oral melatonin and 24% sucrose for pain management during retinopathy of prematurity screening: a randomized controlled trial - Behura, Sushree Smita; Dhanawat, Avantika; Nayak, Biswajit; Panda, Santosh Kumar (The Turkish Journal of Pediatrics, 2022)
Background. Preterm neonates perceive multiple painful procedures during Neonatal Intensive Care Unit (NICU) stay, having long term neurobehavioral effects. This study aims to compare the analgesic efficacy of oral melatonin with 24% sucrose in neonates during retinopathy of prematurity (ROP) screening. Methods. A prospective, non-blinded, randomized controlled trial was conducted in a tertiary care NICU. All preterm neonates with gestational age (GA) < 34 weeks or birth weight (BW) < 2000 grams eligible for ROP screening were randomized into oral melatonin (4 mg/kg) and oral 24% sucrose (0.5 ml) groups. Both groups received standard non-pharmacological measures and topical proparacaine. The intensity of pain was measured by Premature Infant Pain Profile (PIPP) score during the procedure, at 1st and 5th minutes following the procedure and compared between the two groups by Mann-Whitney U test with p value < 0.05 considered as significant. Results. A total of 60 preterm neonates were randomized with 30 neonates in the melatonin (median [interquartile range] GA: 30.86 [3.78] weeks, BW: 1160 [430] grams) and 30 neonates in the 24% sucrose (median [IQR] GA: 29.29 [4.68] weeks, BW: 1070 [315] grams) group. The median PIPP score during the procedure in the melatonin and sucrose groups were 17 and 16, respectively (p=0.64). The median (Q1-Q3) PIPP score at the 1st minute was significantly lower among the melatonin group (7 [5.25-10]) vs 24% sucrose group (9.5 [7.25-11]) (p=0.02); and at the 5th minute, the median (Q1-Q3) PIPP scores in the melatonin group (5 [4-6]) was comparable to the 24% sucrose group (5.5 [3.25-7]) (p= 0.52). Conclusions. Oral melatonin is not inferior to oral 24% sucrose for pain management during ROP screening.
Keywords: analgesic; melatonin; neonate; retinopathy of prematurity